Patarei vangla [Patarei Prison] - Maripuu, Meelis (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2016)
The article discusses the history of the Tallinn central prison, also known as Patarei Prison through 1920–1944. The sea fort built at the beginning of the 19th century – the Kalaranna Fort – was converted into a prison in 1920, as all the former Tallinn prisons had been either destroyed or repurposed. In the 1920s and1930s, the prison was used for detaining criminals as well as people convicted of acts against the Republic of Estonia, both communists and members of the radical right-wing Union of Participants in the Estonian War of Independence in the second half of the 1930s. The majority of the political prisoners were granted amnesty, but the performance programme of the people’s revolution staged aft erthe occupation of Estonia in 1940 still included the liberation of political prisoners. In 1940–1941, the Patarei Prison was used for detaining enemies of the Soviet power, who were mainly state, local government and public figures, military officers and policemen of the Republic of Estonia. Most of them were taken into the Gulag prison camps or executed in 1941. Through 1941–1944, the Patarei Prison was used for detaining persons arrested by the German occupation forces, both participants in communist activities 1940–1941 and members of the national opposition, as well as Jews brought from other countries. The prison was emptied upon the German departure from Tallinn in September 1944; some prisoners were released, but most were taken to the Stutthof concentration camp near Danzig. After Estonia was occupied by the Red Army in autumn 1944, the prison was again filled with political prisoners of the occupying Soviet power.